Demographic transition and economic growth in Sri lanka - Thayaparan, A. (University of Jaffna, 2010)
Demographic changes provide the best understanding to the policy makers to set their priorities for future planning of the country. During the past six decades, Sri Lanka has undergone significant demographic changes, and it has been experiencing a contracting population for the last four decades and the total fertility rate has been declining. Objective of this study is to examine the impact of demographic transition variables on economic growth in Sri Lanka for the period 1990-2009. For this purpose, gross domestic product at current market prices was taken as dependent variable and demographic variables such as infant mortality rate, total fertility rate, labour force participation and midyear population size were considered as independent variables. Secondary data were collected from economic reviews and annual reports of Central Bank of Sri Lanka. Statistical techniques such s growth models and log-log models were applied. Results of the growth models suggest that gross domestic product at current market prices grew at the rate of 13.9%, infant mortality rate has declined by 4%, fertility rate has decreased by 1.3% and population growth has increased by 0.9% for the study period. Results of the log-log model implies that total fertility and population growth rates have positive contribution to the gross domestic product while labour force participation and infant mortality rates have negatively contributed to it and they are significant at 5% level except labour force participation. It is concluded that demographic transition can have significant effect on economic growth of Sri Lanka. Declining in fertility and infant mortality rates, changing of age structure, an increasing life expectancy, changes of women status and all these factors have more powerful to force the demographic transition in Sri Lanka.
Keywords: Demographic transition; Total fertility rate; Infant mortality rate; Economic growth